Dying and death : inter-disciplinary perspectives - Kasher, Asa (At the interface/probing the boundaries ;, 2007)
Annotation Death is a topic people are reluctant to ponder. Neither is dying a process that is usually being openly discussed. However, on a variety of occasions, dying and death are on a person?s minds, under some sensitive circumstances, he or she are eager to discuss with a close person, a friend, a professional. The present volume, the second in the Series on Dying and Death, is meant to enrich personal experience of dying or death by providing its reader with knowledge and understanding of some aspects of dying or death.